Scope fo Focus Particles: Abstract Only in Korean - Lee, Youngjoo (Proceedings of Sinn und Bedeutung, 2019)
The focus particle man ‘only’ in Korean shows different scopal behavior depending upon ist syntactic environment. This non-uniform scope pattern cannot be accounted for if the particle is a scope-bearing element. This paper argues that the particle man is not a scope-bearing element, but an agreement morpheme that indicates the presence of a null head ONLY. Under this proposal, the particle man does not carry the exhaustive meaning of only, but the null head does. Therefore, it is the position of the ONLY head, not that of the particle, that determines the scope relation with respect to other quantificational elements. This paper also claims that there is a strong correlation between syntax and morphology (cf. Baker’s Mirror Principle). Thus, the relative order among the particle, case marker, and postposition reflects the hierarchy of corresponding functional heads. This helps detect the position of the ONLY head. The proposed analysis accounts for the scope patterns without making special stipulations about man-phrases.